Herding Behavior : Analysis of Stock Investor Behavior on the Indonesian Stock Exchange - Handayani, Sri Astuti; Atikah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the herding behavior of LQ-45 shares on the Indonesia Stock Exchange for the 2021-2023 period and determine the influence of market returns and market capitalization on herding behavior. The total sample in this study was 58 companies listed in the LQ-45 stock index for the 2021-2023 period. The analytical method used is Generalized Least Square (GLS) analysis. The research results show that there is no herding behavior on the Indonesian Stock Exchange for the 2021-2023 period, which means investors are rational and do not follow market movements or the actions of other investors. This research also found a relationship between market capitalization and herding behavior, where the greater the market capitalization, the lower the herding behavior. This research makes an important contribution to understanding market behavior and the factors that influence it.